The Baska Mask® -A new concept in Self-sealing membrane cuff extraglottic airway devices, using a sump and two gastric drains: A critical evaluation - Tom van Zundert; Stephen Gatt (Wolters Kluwer Medknow Publications, 2012)
Background: In this study, we evaluated the performance of the Baska Mask® , a new extraglottic airway device (EAD) for use in anesthesia in adult patients undergoing a variety of surgical interventions. Materials and Methods: The self-recoiling membrane distally open cuff silicone mask consists of an anatomically curved airway tube with: (1) a bite block over the full length of the airway; (2) a self-sealing membranous variable-pressure cuff which adjusts to the contours of the mouth and pharynx; (3) a large sump cavity with two aspiratable gastric drain tubes; together with a number of special features such as (4) a tab for manually curving the mask to ease insertion; and (5) a suction elbow integral to one port with a second port acting as a free air flow access. The cuff of the Baska Mask® is not an inflatable balloon, but a membrane which inflates on every breath during intermittent positive pressure ventilation (IPPV) to achieve a superior seal when opposed to the larynx. An increase in IPPV pressure increases the oropharyngeal seal. With existing extraglottic airway devices, an increase in IPPV merely increases the leak. Results: Fifty patients with American Society of Anesthesiologists (ASA) physical status I-III were enrolled. We evaluated the "first attempt" and "overall insertion" success rates, insertion time, ease of insertion and removal of the device, oropharyngeal leak pressure, and anatomical position at fiberoptic view. The "first attempt" success rate was high (88%) and "overall insertion" success rates was considered "easy" to "very easy" by the operators in 92% of patients. Removal of the device was considered easy in all cases. The oropharyngeal leak pressure was above 30 cm H 2 O in all patients and the maximum of 40 cm H 2 O was achieved in 82% of the patients. In two patients, no adequate capnogram was obtained, so a smaller size mask was inserted with correction to adequate function. At fiberoptic evaluation of the anatomical position of the masks, the vocal cords could be seen, except in six patients (12%), where only the epiglottis could be visualized. Conclusion: The new EAD Baska Mask® has many novel features which should improve safety when used in both spontaneously breathing and IPPV anesthesia.